2011
DOI: 10.1002/ijc.25843
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of sunitinib malate, a multitargeted tyrosine kinase inhibitor in patients with relapsed or refractory soft tissue sarcomas. Focus on three prevalent histologies: Leiomyosarcoma, liposarcoma and malignant fibrous histiocytoma

Abstract: SUMMARY Soft tissue sarcomas (STS) represent a diverse group of histologic subtypes with targetable molecular alterations, often treated as a single disease. Sunitinib malate is a multitargeted receptor tyrosine kinase inhibitor active in other solid tumors carrying similar alterations (i.e., imatinib mesylate-refractory gastrointestinal stromal tumors). This single-institution phase II study investigated the safety and efficacy of sunitinib malate in three common STS subtypes. Patients with documented unresec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 25 publications
(22 reference statements)
1
70
0
5
Order By: Relevance
“…In particular, Sunitinib has been used in a phase II study to target the soft tissue sarcoma subtypes leiomyosarcoma, liposarcoma, and malignant fibrous histiocytoma, and it is expected to be effective for the treatment of leiomyosarcoma [15,16]. We ultimately used Axitinib in the current case because of the adverse effects caused by other drugs, rendering them unusable.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Sunitinib has been used in a phase II study to target the soft tissue sarcoma subtypes leiomyosarcoma, liposarcoma, and malignant fibrous histiocytoma, and it is expected to be effective for the treatment of leiomyosarcoma [15,16]. We ultimately used Axitinib in the current case because of the adverse effects caused by other drugs, rendering them unusable.…”
Section: Discussionmentioning
confidence: 99%
“…The first line therapy for retroperitoneal leiomyosarcoma is radical resection, and a tumor that involves large blood vessels may be resected with the vessels, followed by vascular remodeling. Chemotherapy is thought to have no significant effects on patient survival time [4], although a recent report concluded that some patients may experience beneficial effects on sunitinib [5]. Isolated iliac artery aneurysm unaccompanied by abdominal aortic aneurysm is also a rare clinical event [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients die within 1 year after time of diagnosis because of poor prognosis [5]. No therapeutic protocol has been defined for adjuvant chemotherapy but sunitinib, a tyrosine kinase inhibitor, has been shown to be beneficial in the phase-II studies [6].…”
Section: Discussionmentioning
confidence: 99%